THE IMPACT OF TUDOR DYNASTY ON FOUNDATION OF THE BRITISH EMPIRE - İbrahim Çağrı ERKUL (International Journal of Eurasia Social Sciences, 2016)
The events and policies which were occurred in England during Tudor Dynasty greatly contributed to the structuring economic, military and intellectual basis of the British Empire. 1583 is acknowledged as the emergence of the British Empire in the literature. Although 1583 was within the long reign of Elizabeth I, Tudor Dynasty’s contribution should be considered as a whole. Therefore Tudor period from 1485 until 1603 will be detailed based on foundation of the British Empire in this study. To better understand this period, the end of the Hundred Years’ War and Wars of the Roses are also among the topics of this study.